2016
DOI: 10.1108/hff-07-2014-0209
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid flow past an impulsively started vertical plate with variable surface temperature

Abstract: Purpose-The purpose of this paper is to focus on the numerical modelling of transient natural convection flow of an incompressible viscous nanofluid past an impulsively started semi-infinite vertical plate with variable surface temperature. Design/methodology/approach-The problem is governed by the coupled non-linear partial differential equations with appropriate boundary conditions. A robust, well-tested, Crank-Nicolson type of implicit finite-difference method, which is unconditionally stable and convergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…They studied the effects of the Rayleigh number, fin length, oscillating amplitude, oscillating period, thermal conductivity ratio (fin to fluid) and the non-dimensional Young's modulus. Other research studies can be found in literature (Ghalambaz and Noghrehabadi, 2014; Ghalambaz et al , 2014a, 2014b, 2019; Noghrehabadi et al , 2012a, 2012b, 2012c, 2013a, 2013b, 2014; Mansour et al , 2016; Ahmed et al , 2013; EL-Kabeir et al , 2007; Rashad, 2008; Rashad et al , 2011, 2017a, 2017b; Gorla et al , 2011; Sivasankaran et al , 2016; Liu et al , 2019; Aly and Pop, 2019; Nasrin et al , 2019; Sreedevi et al , 2019; Hayat et al , 2015; Mohammed et al , 2012; Makinde (2013); Şenay et al , 2019; Prakash and Agrawal, 2016; Rajesh et al , 2017; Khamis et al , 2015; Alsabery et al , 2019; Vemula et al , 2016; Fornalik-Wajs et al , 2019; Sun and Pop, 2014; Malvandi et al , 2017; Thumma et al , 2017; Rawat et al , 2019; Venkateswarlu et al , 2019a, 2019b). In these research works, different nanofluid parameters and various numerical and experimental models were addressed.…”
Section: Introductionmentioning
confidence: 95%
“…They studied the effects of the Rayleigh number, fin length, oscillating amplitude, oscillating period, thermal conductivity ratio (fin to fluid) and the non-dimensional Young's modulus. Other research studies can be found in literature (Ghalambaz and Noghrehabadi, 2014; Ghalambaz et al , 2014a, 2014b, 2019; Noghrehabadi et al , 2012a, 2012b, 2012c, 2013a, 2013b, 2014; Mansour et al , 2016; Ahmed et al , 2013; EL-Kabeir et al , 2007; Rashad, 2008; Rashad et al , 2011, 2017a, 2017b; Gorla et al , 2011; Sivasankaran et al , 2016; Liu et al , 2019; Aly and Pop, 2019; Nasrin et al , 2019; Sreedevi et al , 2019; Hayat et al , 2015; Mohammed et al , 2012; Makinde (2013); Şenay et al , 2019; Prakash and Agrawal, 2016; Rajesh et al , 2017; Khamis et al , 2015; Alsabery et al , 2019; Vemula et al , 2016; Fornalik-Wajs et al , 2019; Sun and Pop, 2014; Malvandi et al , 2017; Thumma et al , 2017; Rawat et al , 2019; Venkateswarlu et al , 2019a, 2019b). In these research works, different nanofluid parameters and various numerical and experimental models were addressed.…”
Section: Introductionmentioning
confidence: 95%
“…Using nanoparticles can cause an increment in the thermal conductivity of nanofluids while the viscosity remains about the same as the base fluid (Shafahi et al, 2010;A gbulut et al, 2021;Sreedevi et al, 2020aSreedevi et al, , 2020b. Shape and size of nanoparticle, concentration and their thermophysical properties are some of the outstanding parameters that have a significant impact on the thermal performance of prepared nanofluids (Reddy et al, 2018a(Reddy et al, , 2018bVemula et al, 2016;Chamkha, 2017a, 2017b). Many valuable research studies have been presented by researchers, which deal with the performance enhancement of PHE using different nanoparticles (Bhattad et al, 2019;Islam et al, 2020).…”
Section: Plate Heat Exchangermentioning
confidence: 99%
“…Turkyilmazoglu (2012) elucidated the heat and mass transfer effects over a vertical and moving flat plate filled with the nanoparticles. Vemula et al (2016) described the impact of thermal radiation on MHD free convective flow of nanofluid over a moving plate. Ghadikolaei et al (2018) deliberate the TiO 2 -CuO nanoparticles with ethylene glycol mixture and shape factor over rotating cone with the adopted physical parameters.…”
Section: Introductionmentioning
confidence: 99%